2014
DOI: 10.1124/jpet.114.219345
|View full text |Cite
|
Sign up to set email alerts
|

MS-275 Inhibits Aroclor 1254–Induced SH-SY5Y Neuronal Cell Toxicity by Preventing the Formation of the HDAC3/REST Complex on the Synapsin-1 Promoter

Abstract: Polychlorinated biphenyl (PCB) exposure has been associated with neurodegenerative diseases, such as Parkinson's disease, amyotrophic lateral sclerosis, and dementia. Neuronal death elicited by the PCB mixture Aroclor 1254 (A1254) has been attributed to an increase in RE-1-silencing transcription factor (REST), which, in turn, correlates with a decrease in the synapsin-1 promoter gene. Although histone deacetylase (HDAC) inhibitors are known to be neuroprotective in several neurologic disorders, the core mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The same TSA concentrations were used in hippocampal dissociated neurons in culture 4 as well as on organotypic slices in culture 5 . MS275 500 nM and MC1568 1 μM concentrations were shown to yield maximal effects after pre-incubation in vitro for dopaminergic cell cultures 56,57 . MC1568 at 1 μM corresponded to a 10 times higher concentration than IC 50 values reported using tumor cell lines in culture 16,17 .…”
Section: Methodsmentioning
confidence: 94%
“…The same TSA concentrations were used in hippocampal dissociated neurons in culture 4 as well as on organotypic slices in culture 5 . MS275 500 nM and MC1568 1 μM concentrations were shown to yield maximal effects after pre-incubation in vitro for dopaminergic cell cultures 56,57 . MC1568 at 1 μM corresponded to a 10 times higher concentration than IC 50 values reported using tumor cell lines in culture 16,17 .…”
Section: Methodsmentioning
confidence: 94%
“…Animal studies have shown exposure to PCBs affect brain health by affecting social behavior [131], increased hyperactivity [132], reduction in learning ability [133], and physiological effects on the brain such as neuronal degradation [132,134], neuronal loss and damage [135], and susceptibility to amyloid stress and reduced expression of synaptic proteins [134]. In in-vitro models, PCBs have shown to cause neuronal cell death [136] and interfere with estrogen’s neuroprotective effects on neurons and brain cells [137]. In a study using ovariectomized, estradiol-replaced ewes, the VEGF/VEGFR systems is affected by PCBs, which therefore affect the production of cerebrospinal fluid [138].…”
Section: Epidemiologic and Experimental Evidence Of Brain Health Dmentioning
confidence: 99%
“…For immunoblotting, 100 μg of sample for BDNF and 50 μg of sample for all other proteins were separated via SDS-PAGE and transferred to PVDF membranes. After transfer, the membranes were blocked for 2 h at room temperature with 5% non-fat milk in phosphate-buffered saline (PBS) and then incubated at the dilution of 1:1000 in 5% non-fat milk with the following primary antibodies: anti-Sp1, anti-Sp3, anti-Sp4, anti P-ERK, anti-ERK-, anti P-p38, anti-p38, anti P-JNK, anti-JNK, anti-HDAC1, anti-HDAC2, anti-HDAC3, anti-caspase 3, anti-α-tubulin and anti-β-actin, that were already used (Formisano et al, 2015a,b; Guida et al, 2015b), anti-HDAC4 (cod. sc-11418, 1:1000 polyclonal rabbit antibody; Santa Cruz Biotechnology), anti-HDAC5 (cod.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been demonstrated that HDACs 1, 2, and 4 exert a neurotoxic effect after brain ischemia (Formisano et al, 2015b; Yuan et al, 2016), HDAC3 and HDAC5 can induce cell death of cerebellar granule neurons (CGN) (Bardai and D'Mello, 2011), and HDAC6 inhibition protects against oxidative stress-induced neurodegeneration (Rivieccio et al, 2009). On the other hand a pan HDAC inhibition has been found to be neuroprotective in vitro against the neurotoxicity of bis (2-ethylhexyl) phthalate (DEHP) (Guida et al, 2014), Polychlorinated Biphenyls (PCB) (Formisano et al, 2011, 2015a), and MeHg (Guida et al, 2015b). Recently, it has also been shown that the mercury-containing organic compound Thimerosal induces an increase of the HDAC4 isoform (Guida et al, 2015b, 2016) determining neuronal cell death, but the molecular mechanism of this effect is still unrevealed.…”
Section: Introductionmentioning
confidence: 99%